The Framework of Using Mobile-Learning in Higher Vocational Colleges with Extended UTAUT Model - Tang, Weike; Chaveesuk, Singha; Chaiyasoonthorn, Wornchanok (My University, 2024)
With the development of mobile communication technology, mobile learning has become a significant medium of higher education, especially during the COVID-19 outbreak. The large-scale mobile learning is a deep combination of teaching and modern information technology. In this context, the analysis of the factors affecting the mobile learning behavior of students is helpful to promote the process of the integration of online education and offline education. This study aims to propose a conceptual framework of influencing factors of students' using mobile-learning in higher vocational colleges based on an extended UTAUT model by including self-efficacy, personal innovativeness and content quality, from the perspectives of students.
Keywords: content quality; mobile-learning; personal innovativeness; self-efficacy; UTAUT